The Pasinetti Paradox Revisited - Moore, B. J. (Review of Economic Studies, 1974)
Journal Article The Pasinetti Paradox Revisited Get access B. J. Moore B. J. Moore Wesleyan University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 2, April 1974, Pages 297–299, https://doi.org/10.2307/2296719 Published: 01 April 1974